1e Biënnale Beeldend West-Vlaanderen. - 1e Biënnale Beeldend West-Vlaanderen, 1986; Brutin, Hugo; Debucquoy, Roland (Sint-Baafs-Vijve : André Demedtshuis, 1986)
Bouttens, Philippe ; Callens, Mario R.G. ; Clarysse, Clark ; Decock, Gilbert ; Delvoye, Wim ; Deprez, Jean-luc ; Devriendt, Robert ; Dewaele, Daniel ; Elias, Etienne ; Hoorne, Emiel ; Lenoir, Lut ; Moerman, Piet ; Perneel, Paul ; Roelstraete, Stefaan ; Rubens, Albert ; Scherpereel, Koen ; Soubry, Bart ; Sweetlove, William ; Swimberghe, Gilbert ; de Kerckhove, Jan Van ; Van Doorslaer, Etienne (Maur-Etienne) ; Verbeke, Jan Karel ; Verbeke, Ludo ; Verduyn, Jacques ; Vermeersch, Rik ; Vermoere, Gerda ; Willocx, André
biografie
1e Biënnale Beeldend West-Vlaanderen, André Demedtshuis, Sint-Baafs-Vijve, 1986
Nederlands & Frans & Engels
boek